2019
DOI: 10.1108/ijse-06-2019-0365
|View full text |Cite
|
Sign up to set email alerts
|

Women’s presence in top management and the performance of microfinance institutions in West Africa

Abstract: Purpose The purpose of this paper is to investigate the relationship between the presence of women in senior management and the performance of microfinance organizations in the West African Economic and Monetary Union (WAEMU). Design/methodology/approach Using a data set of 266 microfinance institutions (MFIs) for the period 2013–2017, the study assesses the impact of women’s representation in senior management and on the boards of West African MFIs on these institutions’ financial and social performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
2
16
1
1
Order By: Relevance
“…Approximately, a 1% increase in female representation on the boards of an MFI causes between 1% and 7% decline in its financial performance in the short run. These results contradict the studies that reported the positive influence of board gender diversity on the financial performance of MFIs (Bassem, 2009; Mersland & Strøm, 2009; Chakrabarty & Bass, 2014; Strøm et al., 2014; Augustine et al., 2016; Vishwakarma, 2017; Chen et al, 2018; Green & Homroy, 2018; Boubacar, 2019; Song et al, 2020) and uphold the negative effect hypothesis in the empirical literature (Adusei, 2019; Yang et al., 2019; Boehe & Cruz, 2013; Ujunwa, 2012). Therefore, hypothesis H 1 is unsupported.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Approximately, a 1% increase in female representation on the boards of an MFI causes between 1% and 7% decline in its financial performance in the short run. These results contradict the studies that reported the positive influence of board gender diversity on the financial performance of MFIs (Bassem, 2009; Mersland & Strøm, 2009; Chakrabarty & Bass, 2014; Strøm et al., 2014; Augustine et al., 2016; Vishwakarma, 2017; Chen et al, 2018; Green & Homroy, 2018; Boubacar, 2019; Song et al, 2020) and uphold the negative effect hypothesis in the empirical literature (Adusei, 2019; Yang et al., 2019; Boehe & Cruz, 2013; Ujunwa, 2012). Therefore, hypothesis H 1 is unsupported.…”
Section: Resultscontrasting
confidence: 71%
“…Apart from female directors being more efficient and active monitors than male directors (Adams & Ferreira, 2009), they are also more independent because they are not part of the “old boys” network (Carter, Simkins & Simpson, 2003). As a result, they improve the performance of firms (Song et al., 2020; Boubacar 2019; Bennouri et al., 2018; Chen et al., 2018; Green & Homroy, 2018; Vishwakarma, 2017; Darko, Aribi & Uzonwanne, 2016; Strøm et al., 2014; Hartarska & Nadolnyak, 2012). The literature attributes this positive impact to the benefits of heterogeneity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We control for board size measured by the number of directors on the boards of MFIs. Most studies find evidence of improved financial performance with a larger board size (Boubacar, 2019; Datta et al, 2020; Kiel & Nicholson, 2003). Such studies argue from the resource dependency point of view that larger boards create better and more critical resources such as connections with key organizational stakeholders and other business partners, offering different opinions that can enrich debates, increase diversity in terms of gender, professional expertise, nationality, and so forth, which help improve corporate decisions and ultimately affect performance positively (Barnhart & Rosenstein, 1998; Pfeffer, 1972; Pfeffer & Salancik, 1978).…”
Section: Econometric Strategymentioning
confidence: 99%
“…Based on the organizational ladder of MFIs, women can participate in three different important management positions – board members, managers, and loan officers (see Figure 1). Behavioral economics suggest the presence of a variation in economic decisions between male and female (Hartarska, Nadolnyak, & Mersland, 2014), and that the effects of women on various dimensions of MFIs performance (e.g., financial sustainability & social outreach) were significantly positive in general (Augustine et al, 2016; Boubacar, 2019; Ghosh & Guha, 2019; Gudjonsson, Kristinsson, Gylfason, & Minelgaite, 2020; Strøm, D'Espallier, & Mersland, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although, the role of women on the performance of MFIs is well established through rigorous and empirical research (Adusei, Akomea, & Poku, 2017; Bibi, Balli, Matthews, & Tripe, 2018; Boubacar, 2019; Ghosh & Guha, 2019; Gudjonsson et al, 2020; Memon, Akram, & Abbas, 2020; Pedrini, 2018; Vishwakarma, 2017), very little is known of the manifestation of women in the management role and clients base of the South Asian microfinance market. With the recent and remarkable progress in socio‐economic development of the South Asian countries, it is deemed important to examine how it has impacted gender diversity, particularly in the MFIs workforce.…”
Section: Introductionmentioning
confidence: 99%